Pengaruh Model Pembelajaran Berbasis Masalah dan Ekspositori dengan Keterampilan Proses Sains Terhadap Hasil Belajar Fisika Siswa Kelas VIII MTsN 1 Mataram Tahun Ajaran 2014/2015 - Hardiyanto Hardiyanto; Susilawati Susilawati; Ahmad Harjono (Department of Physics Education, Universitas Mataram, 2015)
This research aims to (1) reveal the effect of problem based and expository learning towards physicsÃ¢â¬â¢ learning outcomes, (2) uncover the effect of studentsÃ¢â¬â¢ science process skill towards physicsÃ¢â¬â¢ learning outcomes, (3) reveal the interaction between studentsÃ¢â¬â¢ science process skill and their physicsÃ¢â¬â¢ learning outcomes. This study is a quasi-experimental study applying factorial design 2 x 2. The study was conducted from November 2014 to May 2015.ÃÂ The population of this research is the whole students of class VIII which comprises of 9 classes in MTS Negeri 1 Mataram. The purposive sampling was chosen as the sampling technique for this study, in which class VIII-8 acted as the experiment class and class VIII-7 as the controlled class. The data collection encompasses data of science process skill, and studentsÃ¢â¬â¢ physicsÃ¢â¬â¢ learning outcomes (in the cognitive, affective, and psychomotor domains) towards the main material of light. Technique of collecting data of science process and physicsÃ¢â¬â¢ learning outcomes in affective and psychomotor domains were done by using observation sheet with certain criteria, while cognitive domain was done through the test.ÃÂ The test instrument has previously been through validity test, reliability test, difficulty level, and discrimination index. The data obtained were firstly tested their normality and homogeneity, then continued by the testing of the hypothesis by using two-way analysis of variance (ANOVA). Data analysis technique was done by using ANOVA 2x2 with different cell. The result of this study shows that (1) problem based and expository learning affects physicsÃ¢â¬â¢ learning outcomes, (2) studentsÃ¢â¬â¢ science process skill affects their physicsÃ¢â¬â¢ learning outcomes, and (3) there is no interaction between science process skill and studentsÃ¢â¬â¢ learning outcomes.